Auroral wave structures and ballooning instabilities in the plasma sheet. Issue 10 (16th October 2013) - Xing, Xiaoyan; Liang, Jun; Spanswick, Emma; Lyons, Larry; Angelopoulos, Vassilis
Abstract [1] Auroral wavelike structures extended in the east‐west direction along preexisting arcs are often observed to precede the auroral poleward expansions initiated along that arc. These wave structures are suggested to be the manifestation of ballooning/interchange instabilities in the near‐Earth plasma sheet that may play crucial roles in leading to substorm expansion. The triggering and the development of the ballooning instability in the MHD regime can be evaluated with theory and numerical simulations; however, observations have never shown how these instabilities are initiated in the plasma sheet. In order to examine the instability triggering, we take advantage of the THEMIS ground all‐sky‐imagers and NORSTAR‐NASCAM multiwavelength imagers together with a multi‐spacecraft conjunction to identify the auroral wave structures and to examine the dynamics in the plasma sheet. We show in a case study that the MHD ballooning instability criterion is violated near X = −11 RE in the plasma sheet starting about 1.5 min prior to the initiation of the auroral wave structures. The estimated Alfvénic transit time is slightly larger than 1 min, indicating that the observed auroral signatures are correlated with the ballooning instability developing in the plasma sheet and propagating to the ionosphere along field lines. Magnetic field wavelet analysis shows the initiation of the perpendicular disturbances between 0.01 and 0.02 Hz correlated with the calculated onset of the instability perturbations at the same location, supporting the identification of the localized ballooning instability. At the more tailward region of X ~ −13 RE, enhanced earthward transport toward the unstable region are observed several minutes prior to the instability initiation, which may have modified the pressure spatial distribution and magnetic field topology in the near‐Earth region, leading to the violation of the instability criterion. The further development of the instability may play a crucial role for the aurora explosive expansion.